Precedents in architecture : analytic diagrams, formative ideas, and partis - Clark, Roger H.; Pause, Michael (Hoboken, New Jersey : John Wiley & Son, Inc., 2012)
Precedents in Architecture, Fourth Edition provides a vocabulary for architectural analysis that illuminates the works of leading architects and aids architects and designers in creating their own designs. Thirty-eight leading architects are represented in this updated edition through an analysis of more than 100 buildings that are assessed using a diagrammatic technique applicable to any building. This impressive collection includes fourteen new buildings and seven new, innovative architects distinguished by the strength, quality, and interest of their designs. It delivers valuable guidance in analyzing architectural history as an evolutionary process by exploring the commonality of design ideas reflected in a broad range of structures by internationally renowned architects. Both novices and seasoned professionals will find Precedents in Architecture, Fourth Edition to be a very useful tool for enriching their design vocabulary and for the ongoing assessment of buildings found in today$1 (Bs evolving landscape.s
Analysis : Alvar Aalto ; Tadao Ando ; Erik Gunnar Asplund ; Stephanie Beel ; Peter Q. Bohlin ; Mario Botta ; Filippo Brunelleshi ; David Chipperfield ; Sverre Fehn ; Romaldo Giurgola ; Nicholas Hawksmoor ; Herzog & de Meuron ; Steven Holl ; Toyo Ito ; Louis I. Kahn ; Tom Kundig ; Le Corbusier ; Claude Nicholas Ledoux ; Sigurd Lewerentz ; Edwin Lutyens ; Brian MacKay-Lyons ; Richard Meier ; Rafael Moneo ; Charles Moore ; Glenn Murcutt ; Jean Nouvel ; Andrea Palladio ; Thomas Phifer ; Henry Hobson Richardson ; James Stirling ; Louis Sullivan ; Yoshio Taniguchi ; Guiseppe Terragni ; Ludwig Mies van der Rohe ; Robert Venturi ; Frank Lloyd Wright ; Peter Zumthor -- Formative ideas : Plan to section of elevation ; Unit to whole ; Repetitive to unique ; Additive and subtractive ; Symmetry and balance ; Geometry ; Configuration patterns ; Progressions ; Reduction -- Index.
Keywords: ARCHITECTURAL DESIGN